Hazard Deaggregation for Indonesia - L.L. Makrup; Masyhur Irsyam; I Wayan Sengara; Hendriyawan Hendriyawan (Jurnal Teknik Sipil, 2010)
Abstract. Hazard deaggregation is required in seismic hazard analysis in order to determine the controlling magnitudes and distances for particular return periods of earthquakes. These magnitude and distance are required for physical interpretation of the results from probabilistic seismic hazard analysis and to take certain engineering decisions. This paper presents a development of hazard deaggregation for Indonesia. The deaggregation process is started by calculating the ground shaking with hazard level 10% probability of exceedance in 50 years. In this study, the deaggregation hazard map was analyzed using total probability method and by applying three dimensional (3-D) source models and recent seismotectonic parameters. Three source models were used in this analysis, namely: subduction zones, transform fault zones and background source zone. Indonesian earthquake source models were constructed and published attenuation relations to calculate the peak ground acceleration for rock site conditions were used in the analysis. The recurrence rates and sizes of historical earthquakes on known and inferred faults and across zones were determined from modified earthquake catalog. The results of this study are deaggregation hazard maps of Indonesia for 10% probability of exceedance in 50 years.Abstract. Deagragasi hazard diperlukan dalam analisis seismic hazard untuk menentukan jarak dan magnitude kendali untuk perioda ulang gempa tertentu. Jarak dan magnitude ini digunakan untuk interpretasi fisik terhadap hasil dari analisis seismic hazard probabilistik dan untuk mengambil keputusan tentang hal yang bersifat keteknikan. Paper ini memberikan hal berupa pengembangan deagregasi hazard untuk Indonesia. Proses deagregasi dimulai dengan menghitung goncangan tanah dengan level hazard 10% probabilitas terlampaui dalam jangka waktu 50 tahun. Dalam studi ini, deagregasi hazard diananlisis menggunakan metoda probabilitas total dengan mengaplikasikan model sumber gempa tiga dimensi dan parameter seimotektonik terbaru. Tiga model sumber gempa digunakan dalam analisis ini yaitu sumber gempa zona subduksi, transform fault dan sumber background. Model sumber gempa Indonesia telah dikembangkan dan fungsi atenuasi yang terpublikasi digunakan untuk menghitung percepatan tanah puncak untuk kondisi site batuan. Ukuran dan laju keberulangan gempa-gempa histori pada fault yang sudah dikenal maupun fault yang keberadaanya masih dalam dugaan dan juga pada zona yang lain ditentukan dari katalog gempa yang telah dimodifikasi. Hasil dari studi ini adalah berupa peta deagregasi hazard untuk Indonesia dengan 10% probabilitas terlampaui dalam jangka waktu 50 tahun